Pendampingan Kelompok Mahasiswa dalam Meningkatkan Nilai Branding UMKM Lokal di Desa Blado Kecamatan Blado Kabupaten Batang - Setiawan, Hendy; Choirunnisa, Choirunnisa; Meriwijaya, Meriwijaya; Erison, Yendra (PUSAT PENELITIAN DAN PENGABDIAN PADA MASYARAKAT (PPPM) POLITEKNIK NEGERI SAMBAS, 2025)
Success in creating local MSME product branding is a strategy for MSME players to grow. This is because without innovative product branding, local MSME players will not be able to survive. Only through attractive MSME branding will the product's market share be able to extend beyond regional boundaries. The purpose of this article is to describe that creating local MSME branding is really needed by MSME actors in Blado Village. Moreover, its implementation is supported by the presence of KKN students so that the mentoring process can be carried out. The mentoring service program for KKN students is important because they become facilitators who relate directly to the MSME community. Therefore, the method used in this service is a method of mentoring KKN students which it is hoped that the students will be able to translate this into society. The results show that program assistance to KKN students can be implemented well because students as facilitators to the community are able to carry out their duties with significant acceptance from the community of MSME actors.